TEST DIAGNOSTICS OF COMPUTER SYSTEMS HARDWARE AND SOFTWARE - V. N. Yarmolik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The main scientific and practical results on test diagnostics of hardware and software of computer systems are presented in brief history. More than 500 international and local publications including 17 books and 72 invention certificates reinforce the scientific results. The current state of research and a plan of future research of laboratory are presented.